2015
DOI: 10.1021/ie5047736
|View full text |Cite
|
Sign up to set email alerts
|

Transformation from NaA to MCM-49 Zeolite and Its Catalytic Alkylation Performance

Abstract: The transformation from NaA (LTA) to MCM-49 (MWW) zeolite was achieved in the synergism of hexamethyleneimine (HMI), NaOH, and SiO2, in spite of no common composite build units between LTA (lta, sod, and d4r) and MWW (mel and d6r) structure. NaA (SiO2/Al2O3 = 2.0) was employed as the parent zeolite. The samples prepared at different crystallization stages were characterized by XRD, SEM, 29Si/27Al/13C MAS NMR, and STEM-EDS to investigate the intermediates during the transformation from NaA to MCM-49. As shown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…The X-ray powder diffraction (XRD) patterns collected on a PANalytical X'pert Pro MPD X-ray diffractometer (Philips, Eindhoven, Netherlands) was adjusted to a Cu Kα radiation of 154.06 pm in the range of 2θ from 3 • to 50 • with a scan speed of 4 • /min. Using a paper by Xing and co-workers [40], the relative crystallinity (RC) of metal modified zeolites was obtained by dividing the sums of their diffraction peak intensities at 2θ of 14. The practical atomic composition of catalysts was measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES, Autoscan16, TJA, Seymour Fisher Corporation, USA).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray powder diffraction (XRD) patterns collected on a PANalytical X'pert Pro MPD X-ray diffractometer (Philips, Eindhoven, Netherlands) was adjusted to a Cu Kα radiation of 154.06 pm in the range of 2θ from 3 • to 50 • with a scan speed of 4 • /min. Using a paper by Xing and co-workers [40], the relative crystallinity (RC) of metal modified zeolites was obtained by dividing the sums of their diffraction peak intensities at 2θ of 14. The practical atomic composition of catalysts was measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES, Autoscan16, TJA, Seymour Fisher Corporation, USA).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Cu a (wt%) [40]. c Surface area and pore volume of each of the zeolites were determined by nitrogen physisorption experiments.…”
Section: Zeolitesmentioning
confidence: 99%
“…It was found that the main reaction occurred in the pockets at the surface while coke deposition and oligomerization of ethylene were more favorably produced in the large space of the supercages and 10-R pores. Shu et al [122][123][124] obtained MCM-49 zeolite via the transformation from NaA (LTA) zeolite in the synergism of hexamethyleneimine (HMI), NaOH, and SiO 2 (Fig. 12A).…”
Section: Liquid Phasementioning
confidence: 99%
“…MWW zeolites are attractive materials in several important industrial applications, such as catalytic cracking, hydrocracking, alkylation, oxidation, and isomerization. MWW zeolites possess a layered structure with an abundance of 12MR surface pockets on the surface, which supply places for the reaction of large molecules. MCM-49 is a type of MWW zeolite with a relatively large pore size that exhibits promising properties in liquid-phase alkylation of benzene with ethylene to produce ethylbenzene .…”
Section: Introductionmentioning
confidence: 99%